Legal Protection to General Practitioners Towards Authority Delegation of Medical Services Given by Medical Specialists in Emergency Unit of “Mitra Keluarga” Hospital Tegal - Yanuar Arien Pradana; Tjahjono Koentjoro; Yovita Indrayati (SOEPRA, 2019)
Legal protection provided support and certainty for practitioners or doctors in carrying out their jobs according to service standard, competence and authority. However, the general practitioners who were on duty in the emergency units (ERs), in performing emergency services, we are often instructed by a medical specialist through telephone talk to perform medical actions as needed by the patients. The authority delegation, from a medical specialist to a general practitioner, could factually be full of potential errors whereas there had not been any legislation regulating such authority delegation. Therefore, it would possibly raise ethical and legal accountability matters for the general practitioners caused by the authority transfer between the physicians.This legal research was qualitative research applying analytic descriptive and socio-legal studies approaches, so the discussion covered legal aspects beside social aspects about authority delegation between the two types of practitioners or doctors at ER. The data gathered were both primary and secondary data by involving general practitioners working at the ER of “Mitra Keluarga” Hospital and medical specialists of the same hospital. Besides, the data were also got from the Hospital Director and the Chairman of the Medical Committee.There was no legislation regulating authority delegation of medical specialists to general practitioners so that the internal rules of “Mitra Keluarga” hospital did not regulate such authority delegation. Likewise, legal protection to general practitioners of the ER of “Mitra Keluarga” hospital had not been regulated in detail within the internal rules of “Mitra Keluarga” hospital. However, such legal protection could be attributed to all policies issued by the hospital, such as labour and operational standards applicated in the hospital. The authority delegation from a medical specialist to a general practitioner working at the emergency unit could be matched by authorization as applicable in civil law. Ethically and legally, any medical practice had an inherently legal liability to ensure the patient’s safety.